Factor V from Human Plasma - Surgenor, Douglas M.; Wilson, Nancy A.; Henry, Anne S. (Thrombosis and Haemostasis, 1961)
A method is described for the partial purification of a human plasma factor which accelerates the conversion of prothrombin to thrombin in the presence of tissue thromboplastin. This factor may be dried from the frozen state, and may be kept in stable dry form for long periods of time. The quantitative assay of this activity is done in a classical two-stage prothrombin system using tissue thromboplastin and calcium. From its properties, it is concluded that this activity corresponds to factor V, labile factor and plasma Ac-globulin.Chemical and kinetic studies reveal that human factor V is active in plasma and is destroyed by thrombin. Human serum has little or no factor V activity.These results thus fail to support the postulated activation of factor V during clotting. All of the kinetic data are consistent with an enzymatic role for factor V in the formation of tissue prothrombin activator (thromboplastin).